A Spatial Analysis Of Settlement Pattern Of Jakham River Basin In Pratapgarh District, Rajasthan - Binda, Varun (European Journal of Applied Sciences, 2021)
In the recent era, in geographical studies, the spatial analysis of settlement has an essential place of research. The focus of the study, to relate settlements to their locational arrangement and their connection with each other. The evolution of settlement patterns in an area is governed by several factors, i.e. physical, cultural, etc. Hence, varied ways in the spatial distribution of settlement are found. In this research paper, the author uses the Nearest Neighbourhood Analysis technique for study. Generally, concentration is located in and around the city centre, and concentration continuously decreases as we go away from the city centre. But in this case of the above research of the Jakham river basin in Pratapgarh district, the situation is reverted. It noticed that uniformity is found in the concentration level and distribution pattern all over the district except in the North-western plain.